Penguatan Komunikasi Bahasa Arab Santri Melalui Hafalan Mufrodat - Abdillah Fatih Zulqarnain; Hari Febriansyah; Pepen Suhendra (STIQ Amuntai, 2025)
Abstract: This study aims to explore the strengthening of students' Arabic communication through mufradāt memorization in Islamic boarding schools. Using a qualitative descriptive approach and a mixed method, this research involves students as the main subject and is conducted in a pesantren that has a structured Arabic learning program. Data was collected through observation, interviews, documentation, and student communication ability tests. The results showed that the application of the mufradāt memorization method significantly increased the number of vocabulary mastered by students, from an average of 50 mufradāt before the intervention to 150 mufradāt after six months. In addition, there was a positive relationship between mufradāt memorization and students' speaking skills, where their confidence in using Arabic also increased. However, the study also identified several obstacles, such as a lack of motivation and monotonous teaching methods. Recommendations to overcome these obstacles include the application of more interactive learning methods, personalization approaches, and the use of technology. This research is expected to contribute to the development of Arabic teaching methods in Islamic boarding schools and improve the communication skills of students in Arabic.Keywords: Strengthening communication, Arabic, mufradāt memorization, santri, pesantren.